053 Multiple Sclerosis Prevalence: Cardiff and Vale population-based cohort. Issue 6 (27th May 2022) - Hawken, Jonathan; Robertson, Neil; Tallantyre, Emma; Wynford-Thomas, Ray; Anderson, Valerie; Loveless, Sam
Abstract : As treatment options expand for all disease phases of MS, accurate epidemiological data reflecting contemporary patterns of disease by direct clinical assessment remain key to planning and delivering services. This study describes disease frequency and phenotype in a South Wales population on 01/01/2019 according to McDonald 2017 diagnostic criteria. 831 MS cases were identified in a population of 496, 413. Prevalence 167/100, 000 (95% CI 156–179); females 236/100, 000, males 97/100, 000, sex ratio 2.5:1 (F:M), mean age 52.6 (range 17–91). Age specific preva- lence was highest in females aged 50–54 (403/100, 000). European population standardised prevalence 189/10, 000. Disease course: 55.3% relapsing, 34.8% secondary progressive, and 9.9% primary progressive disease. 76.1% had a disability assessment and 36% an interval MR brain within 12 months of prevalence day. EDSS: <4.0 (45.3%), 4.0–5.5 (11.2%), 6.0–7.5 (31.2%), 8–9.5 (12.3%). MR brain: 73% stable; 22% active (new T2 ± Gd+); the remainder had features of MS but no relevant comparison scan. 39.6% of patients had prior DMT use of which highly effective treatments 17.3%. These data sets establish a trend of increasing prevalence but remain less than recent estimates from the MS Society (179/100, 000) for Wales, and offer baseline estimates of disease course classification and activity to plan services. drhawken@outlook.com